EVALUASI SIFAT KIMIA DAN FISIK GAMBUT DARI BEBERAPA LOKASI DI BLOK C EKS-PLG KALIMANTAN TENGAH (Evaluation of Chemical and Physical Properties of Peat from Several Locations in Block of C Ex-MRP Central Kalimantan) - I. C., Setiadi,; N., Yulianti,; F.F., Adji, (AGRIPEAT, 2016)
ABSTRACTThis research aims to evaluate of the chemical and physical characteristics from several locations inBlock C Ex-MRP, Central Kalimantan. Sampling was using the simple random sampling method with3 (three) replications point. Laboratory analyzes were carried out at the Department of AgronomyLaboratory and the Analytical Laboratory, University of Palangka Raya. These data were analyzedusing the Term of Reference of Land Research Center (1983) as well as the regression and thecorrelation analysis. The results showed that the character of chemistry and fertility of peat from fourlocations in Block C Ex-Mega Rice Project in Central Kalimantan have similarities, except P-availableand saturation base in Kanamit Barat (tidal peat) is 2 times higher than in Kalampangan and 3 timeshigher than in Bukit Tunggal (inland peat). Peatsamples of all research locations have advanced levelof decomposition (sapric) with a range of fiber content 10,40-32,59%, bulk density 0.17 to 0.26 g cm-3,thewater content 148,88-368,95% and reddish black color. The relationship patterns showed there istwo patterns of interconnectedness namely positive relationship and negative among the chemicalproperties, physical properties as well as between them. It describes the interaction of peatcharacteristics, which is needs to be considered for the use and management of peatlands in Block CEx-MRP Central Kalimantan.Keywords: Ex-MRP, peat, Central Kalimantan, chemical characteristics, physical characteristics